Search 72,281 tutors FIND TUTORS
Search for tutors
Ask a question
0 0

How do I solve Algebra Equation (2x-1) (x+3)=0?

Tutors, please sign in to answer this question.

1 Answer

According to the Zero Product Principle, if either of the expressions within the parenthesis is equal to zero, the entire thing will be zero. In simpler terms 0*[anything]=0

So, we have two ways to get a solution for x: 2x-1=0, and x+3=0

2x-1=0          +1 both sides
2x=1             /2 both sides
x=1/2 

 


x+3=0          -3 both sides
x=-3

 

We have two solutions: x=1/2, and x=-3